Pengembangan Materi Ajar PAI Integratif Berbasis Outcome Based Education pada Perguruan Tinggi Umum - Muhammad Fikri; Fadriati Fadriati (YASIN, 2026)
Islamic Religious Education (PAI) in general higher education institutions has become a concern in various studies, particularly in relation to increasing the relevance of learning to the competency needs of the 21st century. However, studies that specifically discuss the development of integrative PAI teaching materials based on Outcomes-Based Education (OBE) remain limited. This study aims to develop integrative PAI teaching materials based on OBE that are valid, practical, and relevant to learning outcomes in general higher education institutions. This study used a research and development approach with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study involved subject matter experts, instructional design experts, and students from general higher education institutions as participants in a limited trial, who were selected through purposive sampling. Data were collected through interviews, documentation, expert validation sheets, student response questionnaires, and observation, and were then analyzed using descriptive qualitative analysis and simple quantitative analysis. The results showed that the developed teaching materials met the very valid category based on expert assessment, received very positive responses from students, and had a high level of learning implementation in the limited trial. These findings indicate that the integration of the OBE approach into PAI teaching materials can improve the alignment of learning with the established outcomes and strengthen the contextual relevance of PAI in general higher education institutions. This study contributes to the development of OBE-based PAI learning and broadens understanding of the integration of Islamic values within the framework of competency-based higher education. The conclusion of this study emphasizes the importance of designing PAI teaching materials that are measurable, applicative, and aligned with learning outcomes. The implications of this study include strengthening the design of PAI learning for lecturers and curriculum developers, as well as opening opportunities for further research on the effectiveness of OBE-based teaching materials in various higher education contexts.